2021
DOI: 10.1111/rsp3.12383
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of regional distribution of AKP votes: Analysis of post‐2002 parliamentary elections

Abstract: Electoral politics and regional variation in socio‐economic conditions of individuals receive huge interest in countries with sizable political tension. Even though Turkey has undergone a combination of periods of economic success and a period of economic and political turmoil, it has been governed by a single political party during the last two decades—Adalet ve Kalkinma Partisi (AKP)— Justice and Development Party. This paper examines the determinants of the variation in regional vote shares of AKP between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
(89 reference statements)
0
2
1
Order By: Relevance
“…An increase in female illiteracy rate, often interpreted as reflecting more conservative values, contributes to an increase in the voting share for the JDP in line with the Kayao glu's (2017) findings, with a coefficient second only to the compound growth rate of the region. The old population rate, as a reflective of a region's dependency ratio, increases the vote share of the ruling party, contrary to the findings of the survey-based study by Erdogan and Semerci (2017), and in line with the results from the study by Deniz et al (2021). This study presents a novel finding concerning the positive relationship between domestic migration and an increase in JDP's vote share.…”
Section: Discussion On Jdp's Voting Dynamicscontrasting
confidence: 57%
See 2 more Smart Citations
“…An increase in female illiteracy rate, often interpreted as reflecting more conservative values, contributes to an increase in the voting share for the JDP in line with the Kayao glu's (2017) findings, with a coefficient second only to the compound growth rate of the region. The old population rate, as a reflective of a region's dependency ratio, increases the vote share of the ruling party, contrary to the findings of the survey-based study by Erdogan and Semerci (2017), and in line with the results from the study by Deniz et al (2021). This study presents a novel finding concerning the positive relationship between domestic migration and an increase in JDP's vote share.…”
Section: Discussion On Jdp's Voting Dynamicscontrasting
confidence: 57%
“…Akarca's (2019) study covering 1950 to 2019 confirmed economic voting, highlighting weakened effects with more parties and ideological distance. Deniz et al. (2021) employed panel data analysis covering the period from 2002 to 2018 to explore the fluctuations in JDP's vote shares over time.…”
Section: Literature Review: the Determinants Of Electoral Choice In T...mentioning
confidence: 99%
See 1 more Smart Citation